Performance of stone mastic asphalt incorporating nano titanium modified asphalt binder - Nur Syafiqah Shamimi, Mohd Zali (2022)
Stone mastic asphalt (SMA) is a type of flexible pavement that suit to high traffic area. Therefore, SMA can cater high volume of traffic loads. Over the years, SMA design keeps improving by adding stabilizers, additives, or even modifying the binder. However, this modification sometimes costly and not environmentally friendly. In addition, due to gap graded characteristic of SMA where the aggregate gradation is not well graded (minimum aggregate size variation), SMA suffers a few drawbacks like bleeding and binder drain off during mixing and transporting. Among the potential additive that may improve the properties is nanomaterials. Nanomaterials in asphalt mixture have pique interest lately. Nanomaterials show a potential modifier that can encounter problems in asphalt mix like premature deformation, rutting, and fatigue. Thus, Nano titanium was used in this study with the range of 1% to 5% by weight of virgin bitumen. The modified bitumen is accessed by its physical properties through softening point test, penetration test and rotational viscosity, while for chemical properties, FTIR and XRD are carried out, and SEM-EDX for morphological properties. The laboratory is further performed by assessing the mechanical performance of nano-modified SMA by its resilient modulus, moisture susceptibility, and dynamic creep test. From the results, at 3% addition of nano titanium, the resilient modulus of SMA shows a 50% increasement in strength compared to the unmodified sample for both 25℃ and 40℃. The binder drain down also shows at 2% nano titanium modified sample, the binder drains down is reduced by 91.5%. The same goes for modified binder at 3% for SEM-EDX, which shows more well-dispersed binder components without eliminating the chemical binder elements that are already present. In conclusion, the modification of the binder with nano titanium has influenced the composition of the binder which brings improvements in all aspect of the bitumen which promotes the mechanical performance of the mix. This study is done to improve the mechanical performance of stone mastic asphalt by modifying the binder with nano titanium in hope to obtain a more well enhanced SMA mixture that could contribute to the expressways of Malaysia.